Istota polecenia testamentowego i jego zaskarżalność - Gorczyński, Grzegorz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
Testamentary burden enables the testator to realize objectives impossible to realize with help of traditional testamentary dispositions as appointment of heir or legacy. Depiction the essence of the testamentary burden is impossible without reference to Roman law. In systematic exposition of the Roman law testamentary burden (modus) is mostly presented commonly with condition and term, as the so called additional dispositions of legal acts (accidentalia negotii). In historical development of Roman law modus was however taken over by legacy. Enforceability of testamentary burden is highly controversial in Polish legal writing and judicature. However any doubts it this matter are ungrounded. Statements denying enforceability of testamentary burden can be simply evaluated as being contra legem. After all, art. 985 Polish Civil Code allows for particular persons to demand the performance of a burden. Enforceability of testamentary burden is thus element of its nature as legal institution
Keywords: testamentary burden; enforceability of testamentary burden